Acceptability and continuation of use of the subdermal contraceptive implant among adolescents and young women in Argentina: a retrospective cohort study. Issue 1 (31st December 2023) - Maceira, Daniel; Oizerovich, Silvia; Perrotta, Gabriela; de León, Rodolfo Gómez Ponce; Karolinski, Ariel; Suarez, Natalia; Espinola, Natalia; Caffe, Sonja; Chandra-Mouli, Venkatraman
Abstract: A new public policy was instituted in Argentina for free distribution of subdermal contraceptive implants to women aged 15–24 years old in the public healthcare system. The objective of this study is to determine the extent to which this population adhered to the implant, as well as predictors of continuation. The retrospective cohort study was based on a telephone survey of a random sample of 1101 Ministry of Health-registered implant users concerning the continuation of use, satisfaction with the method and side-effects, and reasons for removal. Descriptive statistics and multivariate regression analysis were used to explore the association between adherence and having received contraceptive counselling, satisfaction, and side effects. We found high levels of adherence (87%) and satisfaction (94%). Common reported side effects were amenorrhoea or infrequent bleeding, perceived weight gain, increased menstrual bleeding and headaches. Multivariate regression analysis indicates that, among adolescents, having received contraceptive counselling increased comfort, while frequent bleeding at six months hindered trust. Participants who had a history of a prior delivery or who had themselves primarily chosen the method were less likely to request the removal of the implant. Our results support the public policy of free implant distribution in the public health sector. This is a sustainable public policy that contributes to equity and access to effective contraception. It is appropriate for adolescents and young women and will also reduce unintended pregnancies. Our results suggest that counselling patients is key prior to insertion of the implant, as it improves acceptability and continuation.